2007
DOI: 10.1016/j.febslet.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Microglial transplantation increases amyloid‐β clearance in Alzheimer model rats

Abstract: Immunization with amyloid-b (Ab) peptides, a therapeutic approach in Alzheimer's disease (AD), reduces brain Ab, and microglial Ab phagocytosis has been proposed as an Ab-lowering mechanism. We transplanted rat microglia into the rat lateral ventricle just after intra-hippocampal Ab injection, and then investigated the contribution of exogenous microglia to Ab clearance. Migration of exogenous microglia from the lateral ventricle to Ab plaque was detected by magnetic resonance imaging and histochemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…Activated microglia have been observed around senile plaques in the brains of AD patients 38,39) and in fact microglia are activated by fibril Aβ. 40) Although microglia are usually in a state of rest and do not damage neurons and tissue, activated microglia can induce neuronal cell and tissue injury by inducing inflammation via the release of inflammatory cytokines, including tumor necrosis factor α and interleukin-1 (IL-1).…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia have been observed around senile plaques in the brains of AD patients 38,39) and in fact microglia are activated by fibril Aβ. 40) Although microglia are usually in a state of rest and do not damage neurons and tissue, activated microglia can induce neuronal cell and tissue injury by inducing inflammation via the release of inflammatory cytokines, including tumor necrosis factor α and interleukin-1 (IL-1).…”
Section: Discussionmentioning
confidence: 99%
“…Animals were monitored until they regained full consciousness. Three days after injection of cells, the mice were terminally anesthetized with Avertin and perfused with heparinized saline (2500 IU/L) for 2 min (Takata et al, 2007;Pihlaja et al, 2008). The brains were removed and frozen in liquid nitrogen and stored at Ϫ80°C until sectioning.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest the potential of exogenous microglia for the cell therapeutic approach in AD. Therefore, we transplanted rat primary cultured microglia into the lateral ventricle of the Aβ-injected rat and found that exogenous microglia accumulated on the Aβ deposits and increased Aβ clearance in the brain of Aβ-injected rat (53). In the study, we transplanted microglia into the lateral ventricle, while Sawada's groups reported that intra-arterially injected microglia but not macrophages can migrate through the intact or injured blood-brain barrier (BBB) to the brain parenchyma (54,55).…”
Section: Microglial Accumulation On Aβ Depositions In Ad Brainsmentioning
confidence: 99%